2016
DOI: 10.17475/kastorman.289754
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Driving Torques on Direct Screw Withdrawal Resistance in OSB

Abstract: This study was performed to evaluate effects of driving torques on direct screw withdrawal resistance (DSWR) in OSB. Pilot hole diameters (1.6, 2, 2.4 mm), embedded screw orientations (edge-, end-and face-) and torque levels, that were obtained from the two main driving torques of seating and stripping, were selected to test on DSWR. The results of the study showed that the pilot hole diameters were needed to be chosen carefully related to the grain orientation and torque level. The DSWR in face orientation wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 4 publications
0
7
0
Order By: Relevance
“…The juniper OSB panels showed comparable or higher results for the screw withdrawal resistance, especially for the Sap and Slabs-W panels, which had significantly higher peak loads for the edge screw withdrawal resistance. The screw withdrawal with pilot hole 2.4mm and torque level 1.5 Nm for southern yellow pine OSB in the research of Tor et al (2016) was 1859N, 1477N, and 2469N for edge-grain, end-grain, and face-grain respectively.…”
Section: Resultsmentioning
confidence: 91%
“…The juniper OSB panels showed comparable or higher results for the screw withdrawal resistance, especially for the Sap and Slabs-W panels, which had significantly higher peak loads for the edge screw withdrawal resistance. The screw withdrawal with pilot hole 2.4mm and torque level 1.5 Nm for southern yellow pine OSB in the research of Tor et al (2016) was 1859N, 1477N, and 2469N for edge-grain, end-grain, and face-grain respectively.…”
Section: Resultsmentioning
confidence: 91%
“…However, opposing behavior was seen between two variables by hardener utilization and should be evaluated by a future study. Because as Tor et al (2016) reported, the structural unity of a product is directly correlated to the connection ability or performance of the members. And, SHR is one of the performance indicators that is adversely affected by soaking to water (Yorur et al 2020).…”
Section: Resultsmentioning
confidence: 98%
“…An increasing trend can be observed in the SET for driving screws into the side of MDF when the pilot hole diameter increased from 0 to 3.2 mm while there was a decreasing trend when the pilot hole diameter increased from 3.2 to 4.4 mm. Tor (2011) found that the SET values for side MDF specimens were 0.38, 0.41, and 0.46 N•m when the pilot hole diameters of 1.6, 2.0, and 2.4 mm drilled whereas the STT values were 1.36, 1.49, and 1.64 N•m with the corresponding pilot hole diameters, respectively.…”
Section: Statistical Analysesmentioning
confidence: 92%